Deteksi Perubahan Garis Pantai Menggunakan Teknik Geospasial, Studi Kasus Kecamatan Tejakula - Aprianti, Hesti; Dharma, IGB Sila; Hendrawan, I Gede; Anggaraini, Nanin (Journal of Marine Research and Technology, 2021)
The coastal area in Tejakula Subdistrict has many potential benefits for local people and the development of the region. Regarding its economic perspective, marine biodiversity can be utilized for tourism development. In terms of culture and history, this area has many archaeological findings ranging from prehistory until the colonial period. However, the recent study from Balai Arkeologi Bali stated the objects were sunk into underwater at a depth of 1-2 meters due to the abrasion process. Therefore, this research discussed the changes of shoreline in the Tejakula Subdistrict area as a preliminary study to protect and preserve its potential values. This research, both in terms of economy, culture, and history.  The calculation of shoreline changes is using the Digital Shoreline Analysis System (DSAS) application with Net Shoreline Movement (NSM) and End Point Rate (EPR) methods. The results showed that the coastal segment in Tejakula District experienced an abrasion change with an abrasion rate of 0.89 m/year based on the SPOT satellite image analysis and 0.17 m/year from Landsat satellite imagery.